PENGARUH MEDIA SOSIAL TERHADAP PERKEMBANGAN BAHASA GAUL PADA SISWA UPT SPF SD INPRES TELLO BARU 1/1 MAKASSAR - Ira Ramdhany; Eka Fitriana HS; Waddi Fatimah; Satriawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Influence of Social Media on the Development of Slang in Students of UPT SPF SD SD Inpres Tello Baru 1/1 Makassar. This research is a quantitative descriptive research using a quantitative approach. The research took place at UPT SPF SD Inpres Tello Baru 1/1 Makassar. The sample in this study is all students of classes IV/A and IV/B consisting of 38 students from classes IV/A and students from classes IV/B, the total number of samples is 19 students, as for the purposive sampling technique. The sampling data collection method used a questionnaire, with data analysis using SPSS 21.0. The results of the descriptive analysis of the influence of social media were in the poor category with an average score of 33.32, and the use of slang was included in the poor category with an average score of 34.68. The results of the Inferential analysis showed that there was a positive influence of the influence of Social Media on the development of slang in students of UPT SPF SD Inpres Tello Baru 1/1 Makassar with a sig value of 0.010 ˂ 0.05.